Liquidity, Reconstitution, and the Value of u.s. Treasury Strips. - Daves, Phillip R; Ehrhardt, Michael C (Journal of Finance, 1993)
An apparent pricing anomaly exists in the market for U.S. Treasury strips: zero-coupon strips created from principal payments typically trade at significantly higher prices than otherwi se identical zero-coupon strips created from coupon payments. In additi on to documenting this phenomenon, this study demonstrates that differences in liquidity and differences in reconstitution characteristics explain much of this price variation.